Line Spacing Tunability in Multiwavelength Random Fiber Laser based on Series of Lyot Filters - Sulaiman A.H.; Gunaseelan J.; Ismail A.; Abdullah F.; Jamaludin M.Z. (Institute of Electrical and Electronics Engineers Inc., 2023)
Erbium doped fiber amplifiers; Polarization; Polarization-maintaining fiber; Erbium dopde fiber amplifier; Laser-based; Line spacing; Lyot filters; Multiwavelength; Multiwavelength random fiber laser; Nonlinear polarization rotation; Random fibers; Tunabilities; Tunables; Fiber lasers